30+ years of P300 brain–computer interfaces. (17th April 2020) - Allison, Brendan Z.; Kübler, Andrea; Jin, Jing
Abstract: Brain–computer interfaces (BCIs) directly measure brain activity with no physical movement and translate the neural signals into messages. BCIs that employ the P300 event‐related brain potential often have used the visual modality. The end user is presented with flashing stimuli that indicate selections for communication, control, or both. Counting each flash that corresponds to a specific target selection while ignoring other flashes will elicit P300s to only the target selection. P300 BCIs also have been implemented using auditory or tactile stimuli. P300 BCIs have been used with a variety of applications for severely disabled end users in their homes without frequent expert support. P300 BCI research and development has made substantial progress, but challenges remain before these tools can become practical devices for impaired patients and perhaps healthy people. Abstract : Brain–computer interfaces (BCIs) are becoming much more prevalent, and many BCIs rely on the P300. BCIs are gaining attention as tools for patients and even for mainstream applications. This article is important because it addresses many issues in P300 BCI R&D that will impact a growing number of people.